PEMBERDAYAAN LEGALITAS PRODUK LOKAL USAHA MIKRO KECIL DAN MENENGAH MELALUI PROGRAM HIBAH MERDEKA BELAJAR KAMPUS MERDEKA DI DESA PUNTUKREJO - Reza Ilham Maulana; Aldi Rizki Khoiruddin; Kadek Dwi Ariani; Tifani Rizki Dianisa; Zufar Maulana Ar-Razaq; Andini Timoer Putri; Keisya Kalyana Mahdy; Yundha Rachmawati; Martina Radin; Elma Dzakya Salsabila Rein Hart; Rysca Indreswari; Muhammad Rustamaji (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Examining the development of the number of Micro, Small, and Medium Enterprises (MSMEs) in Puntukrejo Village, Ngargoyoso District, Karanganyar Regency, where in 2019 there were 15 MSME actors, then increased by 30 MSMEs in 2020, until the latest data on the number of existing MSMEs reached 50 SMEs. The development of the number of MSMEs and the products of Puntukrejo Village is not proportional to the awareness of MSME actors on the importance of managing the legal aspects of MSME products and registering trademark rights to the Directorate General of Intellectual Property of the Ministry of Law and Human Rights. Therefore, with the problem of the legality aspect of MSMEs and the registration of trademark rights, the service team realized a solution idea to be able to overcome these problems. The service team's service activities are carried out based on the Participatory Rural Appraisal (RPA) method. The purpose of the service is to raise awareness and the active role of MSME actors in Puntukrejo Village in managing the legality of MSMEs and registering Brand Rights. In addition, the service team carried out this activity through the MBKM (Merdeka Belajar Merdeka Campus) program. The form of activities carried out are projects in villages ranging from data collection, socialization, assistance in managing the legal aspects of MSMEs, registration of trademark rights, commercialization to preparing reports and publications. As a result of this activity in the form of completing the legality aspect for MSME actors, the creation of a Trademark Rights certificate for MSME actors in Puntukrejo Village, understanding of the commercialization of Trademark Rights for superior products of Puntukrejo Village, and the independence of Puntukrejo Village MSMEs in developing Mark Rights. Abstrak Menelaah perkembangan jumlah pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) di Desa Puntukrejo, Kecamatan Ngargoyoso, Kabupaten Karanganyar yang mana pada tahun 2019 terdapat 15 pelaku UMKM, kemudian meningkat sebanyak 30 UMKM pada 2020, hingga data terakhir jumlah UMKM yang ada mencapai 50 UMKM. Perkembangan jumlah UMKM dan produk-produk Desa Puntukrejo tersebut tidak sebanding dengan kesadaran pelaku UMKM akan pentingnya mengurus aspek legalitas produk UMKM dan mendaftarkan Hak Merek kepada Direktorat Jenderal Kekayaan Intelektual Kementrian Hukum dan HAM. Oleh karena itu, dengan adanya permasalahan terhadap aspek legalitas UMKM dan pendaftaran Hak Merek ini, tim pengabdi mewujudkan ide solutif untuk bisa mengatasi permasalahan tersebut. Kegiatan pengabdian tim pengabdi laksanakan berdasarkan metode Participatory Rural Apprasial (RPA). Tujuan pengabdian adalah menumbuhkan kesadaran dan peran aktif pelaku UMKM Desa Puntukrejo dalam mengurus legalitas UMKM serta mendaftarkan Hak Merk. Selain itu, tim pengabdi melaksanakan kegiatan ini melalui program MBKM (Merdeka Belajar Kampus Merdeka). Bentuk kegiatan yang dilakukan yakni proyek di desa mulai dari pendataan, sosialisasi, pendampingan pengurusan aspek legalitas UMKM, pendaftaran Hak Merek, komersialisasi hingga penyusunan laporan dan publikasi. Sebagai hasil dalam kegiatan ini berupa telengkapinya aspek legalitas bagi pelaku UMKM, terciptanya sertifikat Hak Merek bagi para pelaku UMKM di Desa Puntukrejo, pemahaman mengenai komersialisasi Hak Merek produk unggulan Desa Puntukrejo, serta mandirinya UMKM Desa Puntukrejo dalam mengembangkan Hak Merek.